Supersymmetric Quantum Mechanics of Continuous Topological Insulators - Gamboa-Rios, J; Mendez-Ferrada, F (World Scientific, 2022)
In this paper, we construct a class of quantum systems in a space continuum inspired by results from topological insulator physics. Instead of adding spin-orbit coupling terms suggested by time-reversal invariance as in conventional topological insulators, the terms L~S are determined using supersymmetry as a starting point. This procedure not only restricts the number of possible continuous topological insulators models, but also provides a systematic way to find new continuous topological insulators models. Some explicit quantum mechanical examples are discussed and applications to dark matter physics are also outlined. © 2022 World Scientific Publishing Company.